Fatty Acid and Amino Acid Profile of Brycinus nurse and Tilapia sheriensis from Alau Lake, Maiduguri, Borno State, Nigeria - Bello, M. M.; Ngolmo, E. E. (Nigerian Journal of Animal Science and Technology (NJAST), 2021)
Fishes are consumed for their taste, high protein content, amino acid and saturated fatty acids. However, nutritional information on fishes of Alau Lake is limited. Therefore, the fatty and amino acids profile of Brycinus nurse and Tilapia sheriensis from freshwater Lake of Alau was investigated. Brycinus nurse and Tilapia sheriensis were analysed for fatty acids, amino acids, moisture content, crude protein, crude fibre, ether extract, dry matter, ash and nitrogen free extract using standard methods at the National Research Institute for Chemical Technology (NARICT) Zaria, Kaduna State, Nigeria. Data obtained were subjected to analysis of variance (ANOVA), using SPSS for windows version 20. The results revealed that the fish species had high quality protein. The highest value was recorded for glutamic (29.03) and lowest in aspartic acids (17.85) mg/100g respectively. The highest amino acids values were recorded in Brycinus nurse while Docosahexaenoic and Eicosapentaenoic acids was the dominant polyunsaturated fatty acids in all the species. The fatty acid composition of Brycinus nurse ranged from 0.1 % to 36.89 % and that of Tilapia sheriensis ranged from 0.1% to 32.2%. However, statistical analysis showed no significant difference at P˂0.05 level of significance. Conclusively, the two freshwater fishes Brycinus nurse had high protein – high oil while Tilapia shariensis had high protein – low oil. Both fishes are excellent sources of fatty acids and amino acids, that are good supplement for polyunsaturated omega-3 in the diet.